PENGARUH CORPORATE GOVERNANCE TERHADAP PENGHINDARAN PAJAK (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2011-2014) - Ahmad Reza Dwi Permana; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2015)
This study was conducted to establish the effect of corporate governance consisting of board size, percentage of independent commissioner, and executive’s compensation against tax avoidance. This study was a replication with a modification from the research of Minnick and Noga (2010) examining the corporate governance against tax avoidance proxied by the effective tax rate.The population of this study consists of manufacturing companies listed in Indonesia stock exchange in 2011-2014. Samples in this study consist of 83 sample from 2011, 80 sample from 2012, 76 samples from 2013, 80 samples from 2014, and 319 obsevation of financial reports of manufacturing sompanies. Hypothesis testing was conducted to analyze the data using multiple regression analysis.This study shows that corporate governance has no influence toward tax avoidance. There is no significant effet between the size of commissioner and tax avoidance, there is no percentage of commissioner and tax avoidance, and ther is no significant effect between the executive’s compensation and tax avoidance. It can be concluded that corporate governance does not have any effect of tax avoidance.